Universal franchise 1931-1981 the sri lankan experience - de Silc, K.M. ([Colombo] Dept. of Information, Ministry of State, Democratic Socialist Republic of Sri Lanka, 1981)
"Commemorative volume: fifty years of universal franchise in Sri Lanka."
Keywords: Sri Lanka; democracy; elections; politics; Universal suffrage -- Sri Lanka